Pengaruh Kejelasan Sasaran Anggaran, Pengendalian Akuntansi, Penerapan Akuntansi Sektor Publik Dan Ketaatan Pada Peraturan Perundangan Terhadap Akuntabilitas Kinerja Instansi Pemerintah Kota Pekanbaru - Mentari Cefrida S; Emrinaldi Nur Dp; Mudrika Alamsyah Hasan (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
The purpose of this study is to examine empirically the effect of budget goal clarity, accounting control, public accounting application and compliance with laws and regulations to accountability government performance of pekanbaru. This study use questionnaire to colleting data. Four hyphotesis purpose in this research which analysist by parcial linear square. Data analysis method is using hypothesis testing of Inner Model. Previously conducted analysis, each variable tested for validity and reliability of data using smart software PLS. The result of this research showed budget goal clarity have significant effect to accountability government performance while accounting controls, public accounting application, and compliance with laws and regulations conversely. The result aslo indicate only budget goal clarity have influen to account ability for public sector.Keywords: Budget goal clarity, accounting control, public accounting implementation, adherence to the rule of law, accountability of agency performance